BUDAYA BELAJAR DAN ETHOS BELAJAR PEGAWAI PEMERINTAH - Suryatna1, Ayat (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2006)
This writing describes the interrelationship between learning culture and learning ethics among local government apparatus as a community. The apparatus’ learning culture is commonly shaped by their compulsions to fulfil their daily needs. There are two models of local apparatus learning culture. One is characterized by their etnical milieu; the other develops through work environment. The mixture of those models determines their learning styles, in terms of (1) learning behaviours, (2) learning strategies, and (3) learning actions. A case study for this purpose is conducted on a number of students at Sekolah Tinggi Ilmu Administrasi Negara (School of Public Administration) Lembaga Administrasi Negara (the National Agency for Public Administration) Bandung. The students are government apparatus of various government agencies all over Indonesia. Key words: learning culture, culture ethics, learning ethics, learning aptitude.